Magnetic Hyperbranched Molecular Materials for Treatment of Oily Sewage Containing Polymer in Oilfield Compound Flooding - Qiao, Sanyuan; Liu, Qingwang; Fan, Zhenzhong; Tong, Qilei; Cai, Li; Fu, Yuanfeng (Frontiers in Chemistry, 2022)
With the continuous deepening of oilfield development and the application of tertiary oil recovery technology, the water content of oilfield produced fluids has gradually increased, and a large number of oilfield sewage with complex components has also been produced after oil-water separation, and effective treatment is urgently needed. ASP flooding sewage contains alkali, various surfactants, polymers, microemulsion oil droplets and solid impurities, which are difficult to be effectively treated by traditional water treatment agents and methods. In this paper, APTES was used to modify the nano Fe3O4 coated by tetraethyl silicate (TEOS). The product was used as the ferromagnetic nano core for the iterative reaction of Michael addition and ester amidation to synthesize a magnetic hyperbranched polyamide amine, and its performance in the treatment of ASP flooding wastewater was evaluated experimentally. The preparation of APTES modified Fe3O4@SiO2 (FOSN) product needs to use TEOS to coat Fe3O4 in ethanol aqueous solution environment, and then add APTES dropwise. The first-generation branched product (1-FSMN) was obtained by the reaction of FOSN and methyl acrylate graft product (FOSN-M) with ethylenediamine, and the highest yield was 93.7%. The highest yield of the second generation branched product (2-FSMN) was 91.6%. In this paper, a composite flooding wastewater sample from a block in the Bohai Oilfield was taken. The suspended solids were 143 mg/L, the oil content was 921.09 mg/L, the turbidity was 135 NTU, and the Zeta potential was -47 mV. The third generation hyperbranched polymer (3-FSMN) and its quaternary ammonium salt (3-FSMN-Q) perform best in the appropriate dosage range, with the highest oil removal rate of 97%, suspended solids removal rate of 90.3%, turbidity reduction rate of 86.6% and zeta potential reduction rate of 88%. For 3-FSMN and its quaternary ammonium salt, the gravity/magnetic PAC compound treatment experiment was carried out. In the settlement time of only 5min, 3-FSMN/PAC and 3-FSMN-Q/PAC can achieve the maximum oil removal rate of 87.1% and suspended solids removal rate of 87.3% for polymer containing wastewater from ASP flooding, and 86.3% and 86.0% for 120 mg/L, Its treatment capacity is much better than that of common treatment agent combination (CPAM/PAC).